Advances in pacific basin business, economics and finance. vol. 11 - Lee, Cheng-Few; Yu, Min-Teh (Emerald Publishing Limited, 2023)
Advances in Pacific Basin Business, Economics and Finance (APBBEF) is an annual series designed to focus on interdisciplinary research in finance, economics, and management among Pacific Rim countries. All articles published are reviewed and recommended by at least two members of the editorial board. Topics of interest include, but are not limited to, the following: 1. Policy and management on financial markets and financial institutions; 2. Options, futures, and other derivatives markets; 3. Corporate finance and investment decisions; 4. Insurance and risk management; 5. Accounting, auditing, and taxation; 6. Real esate econimics, finance and regulations; 7. Artificial intelligence and new technology in finance; 8. Monetary and foreign exchange policy; 9. Income, employment, and education; 10. Other economic policies among the Pacific Rim countries. APBBEF is indexed in ABI/INFORM, EconLit, EBSCO, ProQuest, ResearchGate, and Google Scholar. Manuscript submission: mtyu@nycu.edu.tw.
Keywords: Economics -- Pacific Area.; Business -- Pacific Area.; Finance -- Pacific Area.; Mangaement -- Pacific Area.; Business & Economics -- International -- Economics & Trade.; International economics.; elektronické knihy; electronic books